Wartime Deterioration of Young Man’s Life in Yasmina Khadra’s Sirens of Baghdad - Ali Khalaf, Faysal; Ali Ahmad, Dhiya (Opción, 2019)
This paper investigates the multiple reasons which deteriorate the hero’s life during the war that undermines reason and destroys the most vulnerable side of human beings, which is feeling. Violence in all its forms turns the protag- onist into a different man whose heart is filled with a volcano of hatred and despair. Yasmina Khadra’s Sirens of Baghdad( 2008 ), examines the many disasters that resulted from the Euro-American occupation of Iraq post and their effect in turning a young man’s life into destruction. Yasmina Khadra criticizes the western view of the third world as a land steeped in fundamen- talism, extremism and violence, especially Islamic region.